SAT0525 EFFICACY AND SAFETY OF MZR FOR IgG4-RELATED DISEASE. (2nd June 2020) - Kawaai, S.; Fukui, S.; Nakai, T.; Kidoguchi, G.; Ozawa, H.; Ikeda, Y.; Koido, A.; Ohara, Y.; Shimizu, H.; Tamaki, H.; Yamaguchi, K.; Okada, M.
Abstract : Background: IgG4-Related Disease (IgG4RD) is known to cause multiple organ lesions with infiltration of IgG4-positive plasma cells, and patients often have relapses with tapering treatments despite an initial good response to glucocorticoids therapy. Mizoribine (MZR) is an immunosuppressant working as an inhibitor of purine synthesis, which mechanism of action is similar to mycophenolate mofetil. Data regarding the efficacy and safety of MZR on IgG4RD is limited although some previous case reports 1 showed effectiveness for IgG4RD. Objectives: This study aims to assess the efficacy and safety of MZR in patients with IgG4RD. Methods: We retrospectively reviewed charts of IgG4RD patients who used MZR between January 2004 and December 2019 at Immuno-Rheumatology Center in St. Luke's International Hospital, Tokyo, Japan. We investigated basic demographics, involved organs, results of blood tests including IgG and IgG4 titer, and medications used including glucocorticoid and other immunosuppressants (IS). We followed IgG4 titer, dose of glucocorticoid, flare of disease and retention of MZR at the beginning, 6 and 12months after starting MZR. We compared changes in PSL (prednisolone) doses and IgG4 titers over time using Friedman test with Bonferroni correction. We also checked adverse events during follow up. Results: Twenty-two patients with IgG4RD who used MZR were included. Median age was 62 years old, and 15 (68.2%) patients are male. Lacrimal and salivary glands, pancreatitis and retroperitoneal fibrosis were common lesions. All patients were initially treated with glucocorticoids. Flare was observed in 5 (22.7 %) patients before initiation of MZR. The number of patients who continued MZR without flare are 19 (86.4 %) at 6 months, and 14 (73.7 %) at 12 months. IgG4 titer significantly declined at 6 and 12 months from baseline although significant consecutive decrease in PSL dose (Figure 1, 2). Liver dysfunctions are commonest adverse events (n=16, 72.7%) but mild (grade1; n=15, 68.2%) and most cases are apparently due to other reasons. Serious infection (SI) occurred in 3 (13.6%) patients in total follow up, however no SI were observed during 1 year after MZR treatment. Conclusion: MZR can be safely used in patients of IgG4RD with high retention rate, and seemed to have steroid-sparing effect. Prospective comparative studies are needed. References: [1]Nanke Y, Kobashigawa T, Yago T, Kamatani N, Kotake S. A case of Mikulicz's disease, IgG4-related plasmacytic syndrome, successfully treated by corticosteroid and mizoribine, and then by mizoribine alone. Intern Med 49: 1449-1453, 2010. Disclosure of Interests: None declared